Equal Dignity and Agency: Catholic Social Teaching & The Lives of Women - Clark, Meghan J. (Irish theological quarterly, 2025)
Greater inclusion of women is a priority of Pope Francis’s pontificate. He has taken practical steps in appointing women within the Vatican and called for a “deeper theology of women.” Within Catholic social teaching, however, the voices and lives of women remain largely absent. Centring the complex stories from women’s lives gathered through fieldwork, this article argues that women must be embraced as “dignified agents” and not simply as the “doubly poor” or paragons of “heroic daily virtue.” First, I will examine the development of CST on women prior to Francis revealing tensions between the way the tradition treats public vs. private roles. Second, this article will analyse the contribution of Pope Francis. And finally, I will lift up Fratelli Tutti’s approach to the parable of the good Samaritan as a microcosm for the moral life as opening new space for the full lives and dignity of women within the tradition.